1977
DOI: 10.1080/03079457708418246
|View full text |Cite
|
Sign up to set email alerts
|

Propagation and assay of virulent and attenuated JMV Marek's disease‐associated tumour cells

Abstract: SUMMARYJMV tumour cells were shown to cause a lethal lymphoblastic leukaemia in young chickens as well as in chicken embryos. The incubation period was very short but dose-dependent. Chickens died in 4 to 12 days, embryos in 7 to 14 days, after inoculation. Embryo-passaged attenuated JMV (JMV-A) caused the same lesions in embryos as virulent JMV. The dose-response relationship depended on the route of inoculation and on the quality of the tumour cell preparation. Intramuscular (i.m.) inoculation of leukaemic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

1977
1977
1980
1980

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…Previous experiments in our laboratory (Bülow and Weiland, 1977) have shown that cell-free preparations of JMV intended for use in cross-immunisation studies were completely ineffective. Witter and his group concluded from their results (Witter et al, 1975 ;Stephens et al, 1976) that JMV lymphoblasts carried a surface antigen closely related or identical to MD tumour-associated surface antigen (MATSA).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous experiments in our laboratory (Bülow and Weiland, 1977) have shown that cell-free preparations of JMV intended for use in cross-immunisation studies were completely ineffective. Witter and his group concluded from their results (Witter et al, 1975 ;Stephens et al, 1976) that JMV lymphoblasts carried a surface antigen closely related or identical to MD tumour-associated surface antigen (MATSA).…”
Section: Introductionmentioning
confidence: 92%
“…Marek's disease (MD)-derived tumour cells capable of causing a lethal lymphoblastic leukaemia in chickens have been designated as JMV (JM variant) by Sevoian (1967). Studies designed for the biological characterisation of JMV have revealed that virulent as well as attenuated JMV lymphoblasts (JMV, JMV-A) were lacking in rescuable virus (Witter et ai, 1975;Stephens etal, 1976;Bülow and Weiland, 1977). This is inconsistent with the results of other authors who found Marek's disease virus (MDV) or an unspecified herpesvirus associated with JMV (Hamdy and Sevoian, 1973;Hong and Sevoian, 1974;Shieh and Sevoian, 1974;Spencer et al ,1974Spencer et al , , 1976Yoon andKenyon, 1975;Yoon et al, 1976).…”
Section: Introductionmentioning
confidence: 94%
“…Chickens and embryos were from a flock of Rhode Island Red (RIR) chickens which are genetically susceptible to MD and are specific pathogen-free for all common avian viruses (Bülow and Weiland, 1977).…”
Section: Chickens and Chicken Embryosmentioning
confidence: 99%
“…Die Kultivierung der Zellinien RPL-1, MSB-1, HPRS-1 und HPRS-2, die Gewinnung von JMV-Lymphoblasten aus Kuken oder Embryos und die Herstellung von Huhner-Hyperimmunseren gegen JMV sind in einer friiheren Arbeit beschrieben worden (BULOW u. WEILAND, 1977). Zur Herstellung von Antiseren gegen Zellen der Linien RPL-1, MSB-1 und HPRS-2 wurden Kaninchen dreimal in Abstanden von 14 Tagen mit 2-4 X lo8 Zellen i. v. immunisiert und 7 Tage nach der letzten Immunisierung entblutet.…”
unclassified